BMAL1 regulates the initial step of embryo implantation by modulating endometrial cell adhesion and migration - Keita Imai; Yidan Dai; Masanori Ono; Yoshinari Imai; Junya Kojima; Tomoko Fujiwara; Takiko Daikoku; Yoshiko Maida; Hitoshi Ando; Hiroshi Fujiwara; Hirotaka Nishi (Human Cell, 2026)

Nutritional Supplementation and Enhanced Antioxidant Function by Dietary Intake of Selenoneine and Other Selenium Compounds in Red Seabream Pagrus major - Yutaro Shimokawa; Kanako Abe; Mami Ohura; Manae Yamamoto; Hitoshi Ando; Takuma Tohfuku; Michiaki Yamashita; Masakazu Kondo (Marine Biotechnology, 2023)
Selenoneine, 2-selenyl- N α , N α , N α -trimethyl- L -histidine, is the major organic selenium compound in marine fish. To characterize biological antioxidant function of selenoneine in fish, the accumulation of selenoneine and other selenium compounds, i. e., sodium selenite and selenomethionine, in the muscle and other tissues of red seabream. We reared red seabream by feeding of 1% dry pellet containing of sodium selenite, selenomethionine, or selenoneine of body weight twice a day for 4 weeks. After that, we replaced to 1% of normal commercial dry pellet of body weight twice a day for 1 week from the selenium supplementation, and tissue distribution of total selenium was determined. Selenium supplementation with selenoneine, selenomethionine, and sodium selenite enhanced selenium accumulation in the white muscle, kidney, and hepatopancreas in comparison with the control group. By the dietary intake of selenoneine, total selenium concentrations were increased in the white muscle, heart, kidney, spleen, hepatopancreas, brain, and blood cells in a dose-dependent manner during the trials after 2 weeks. Dietary intake of selenoneine as well as sodium selenite and selenomethionine reduced oxidation–reduction potential (ORP). Selenoneine concentrations in the white muscle and blood cells were accumulated for 4 weeks by the selenoneine intake, whereas selenoneine concentration was not elevated by the intake of selenomethionine and sodium selenite, suggesting that tissue selenoneine levels might be derived from only selenoneine-containing diet. The uptake factor of selenoneine from the artificial feed containing selenoneine was calculated to be 0.0062 in the white muscle and 4.0 in the blood. The half-life of total selenium in the blood cells and white muscle were estimated to be 60 days in the white muscle and 30 days in the blood.

Effects of ABCB1 and ABCG2 polymorphisms on the pharmacokinetics of abemaciclib - Akimitsu Maeda; Hitoshi Ando; Kei Irie; Naoya Hashimoto; Jun-ichi Morishige; Shoji Fukushima; Akira Okada; Hiromichi Ebi; Masahide Matsuzaki; Hiroji Iwata; Masataka Sawaki (European Journal of Clinical Pharmacology, 2022)

Dietary Intake of Selenoneine Enhances Antioxidant Activity in the Muscles of the Amberjack Seriola dumerili Grown in Aquaculture - Takuma Tohfuku; Hitoshi Ando; Naho Morishita; Michiaki Yamashita; Masakazu Kondo (Marine Biotechnology, 2021)

Caloric restriction reduces basal cell proliferation and results in the deterioration of neuroepithelial regeneration following olfactotoxic mucosal damage in mouse olfactory mucosa - Hitoshi Iwamura; Kenji Kondo; Shu Kikuta; Hironobu Nishijima; Ryoji Kagoya; Keigo Suzukawa; Mizuo Ando; Chisato Fujimoto; Makiko Toma-Hirano; Tatsuya Yamasoba (Cell and Tissue Research, 2019)

Depositional ages and characteristics of M iddle– U pper J urassic and L ower C retaceous lacustrine deposits in southeastern M ongolia - Hitoshi Hasegawa; Hisao Ando; Noriko Hasebe; Niiden Ichinnorov; Tohru Ohta; Takashi Hasegawa; Masanobu Yamamoto; Gang Li; Bat‐Orshikh Erdenetsogt; Ulrich Heimhofer; Takayuki Murata; Hironori Shinya; et al. (Island Arc, 2018)
Lower Cretaceous lacustrine oil shales are widely distributed in southeastern Mongolia. Due to the high organic carbon content of oil shale, many geochemical studies and petroleum exploration have been conducted. Although most of the oil shales are considered to be Early Cretaceous in age, a recent study reveals that some were deposited in the Middle Jurassic. The present study aims at establishing depositional ages and characteristics of the Jurassic and Cretaceous lacustrine deposits in Mongolia. The Lower Cretaceous Shinekhudag Formation is about 250 m thick and composed of alternating beds of shale and dolomite. The Middle Jurassic Eedemt Formation is about 150 m thick and composed of alternating beds of shale, dolomitic marl, and siltstone. The alternations of shale and dolomite in both formations were formed by lake level changes, reflecting precipitation changes. Shales were deposited in the center of a deep lake during highstand, while dolomites were formed by primary precipitation during lowstand. Based on the radiometric age dating, the Shinekhudag Formation was deposited between 123.8 ±2.0 Ma and 118.5 ±0.9 Ma of the early Aptian. The Eedemt Formation was deposited at around 165–158 Ma of Callovian–Oxfordian. The calculated sedimentation rate of the Shinekhudag Formation is between 4.7 ±2.6 cm/ky and 10.0 ±7.6 cm/ky. Shales in the Shinekhudag Formation show micrometer‐scale lamination, consisting of algal organic matter and detrital clay mineral couplets. Given the average thickness of micro‐laminae and calculated sedimentation rate, the micro‐lamination is most likely of varve origin. Both Middle–Upper Jurassic and Lower Cretaceous lacustrine oil shales were deposited in intracontinental basins in the paleo‐Asian continent. Tectonic processes and basin evolution basically controlled the deposition of these oil shales. In addition, enhanced precipitation under humid climate during the early Aptian and the Callovian–Oxfordian was another key factor inducing the widespread oil shale deposition in Mongolia.

Functions of miR-1 and miR-133a during the postnatal development of masseter and gastrocnemius muscles - Megumi Nariyama; Manami Mori; Emi Shimazaki; Hitoshi Ando; Yoshiki Ohnuki; Tokuhisa Abo; Akira Yamane; Yoshinobu Asada (Molecular and Cellular Biochemistry, 2015)

Concerns about inherited risk of breast cancer prior to diagnosis in Japanese patients with breast complaints - Noriko Ando; Yumi Iwamitsu; Masaru Kuranami; Shigemi Okazaki; Kenji Yamamoto; Masahiko Watanabe; Hitoshi Miyaoka (Familial Cancer, 2011)

Green corolla segments in a wild Petunia species caused by a mutation in FBP2, a SEPALLATA-like MADS box gene - Kiyoshi Matsubara; Katsuyoshi Shimamura; Hiroaki Kodama; Hisashi Kokubun; Hitoshi Watanabe; Isabel L. Basualdo; Toshio Ando (Planta, 2008)

Phylogenetic analysis of the genus Petunia (Solanaceae) based on the sequence of the Hf1 gene - Sumei Chen; Kiyoshi Matsubara; Takahiro Omori; Hisashi Kokubun; Hiroaki Kodama; Hitoshi Watanabe; Goro Hashimoto; Eduardo Marchesi; Laura Bullrich; Toshio Ando (Journal of Plant Research, 2007)

Distribution of self-compatible and self-incompatible populations of Petunia axillaris (Solanaceae) outside Uruguay - Hisashi Kokubun; Makoto Nakano; Tatsuya Tsukamoto; Hitoshi Watanabe; Goro Hashimoto; Eduardo Marchesi; Laura Bullrich; Isabel L. Basualdo; Teh-hui Kao; Toshio Ando (Journal of Plant Research, 2006)

Efficient Transfection Strategy for the Spatiotemporal Control of Gene Expression in Zebrafish - Hideki Ando; Hitoshi Okamoto (Marine Biotechnology, 2006)

Duplication of the S-locus F-box gene is associated with breakdown of pollen function in an S-haplotype identified in a natural population of self-incompatible Petunia axillaris - Tatsuya Tsukamoto; Toshio Ando; Hitoshi Watanabe; Eduardo Marchesi; Teh-hui Kao (Plant Molecular Biology, 2005)

MIC-A polymorphism in Japanese and a MIC-A-MIC-B null haplotype - Miki Komatsu-Wakui; K. Tokunaga; Yoshihide Ishikawa; Kouichi Kashiwase; Satoshi Moriyama; Naoyuki Tsuchiya; Hitoshi Ando; Takashi Shiina; Daniel E. Geraghty; Hidetoshi Inoko; Takeo Juji (Immunogenetics, 1999)

Allelic variants of the human MHC class I chain-related B gene (MICB) - Hitoshi Ando; Nobuhisa Mizuki; Masao Ota; Masaaki Yamazaki; Shigeaki Ohno; Kaori Goto; Yoshihisa Miyata; Kazuo Wakisaka; Seiamak Bahram; H. Inoko (Immunogenetics, 1997)